2016
DOI: 10.1590/s0104-129020162627
|View full text |Cite
|
Sign up to set email alerts
|

Mulher e negra: dupla vulnerabilidade às DST/HIV/aids

Abstract: CorrespondênciaRua Santa Cruz, nº 81, 1º andar, Gerência de Prevenção -CRT-DST-AIDS. São Paulo, SP, Brasil. CEP: 04121-000. 602 ResumoO objetivo deste trabalho é discutir os fatores determinantes da vulnerabilidade das mulheres negras a HIV/aids. Pela descrição e análise de dados socioeconômicos, de incidência e mortalidade de aids e da mortalidade de outras patologias, desenha-se o quadro epidemiológico que ressalta as iniquidades em saúde da população negra e, em particular, das mulheres desse segmento popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
29

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 27 publications
0
19
0
29
Order By: Relevance
“…To analyze the evolution of the cases of HIV-infected pregnant women, we observed an important phenomenon for the current time of the AIDS epidemic in Brazil, which, for decades, was linked to homosexuality; however, its dissemination reached various social segments. For years, groups and/or risk behavior were described, but nowadays, they report a framework marked by heterosexualization and feminization processes (35)(36)(37) . This new scenario demands the recognition of the vulnerability conditions of women to HIV (12) .…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the evolution of the cases of HIV-infected pregnant women, we observed an important phenomenon for the current time of the AIDS epidemic in Brazil, which, for decades, was linked to homosexuality; however, its dissemination reached various social segments. For years, groups and/or risk behavior were described, but nowadays, they report a framework marked by heterosexualization and feminization processes (35)(36)(37) . This new scenario demands the recognition of the vulnerability conditions of women to HIV (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study (4) with the objective of evaluating the inequities in prenatal and childbirth care according to race/color, with data from the research "Birth in Brazil: National Survey Into Labour And Birth" , demonstrated that, compared to white women, postpartum black women were more likely to receive inadequate prenatal care, to have no link with a maternity, to have no companion during delivery, to seek more than one hospital for childbirth and were less likely to receive local anesthesia for the episiotomy. These cumulative disadvantages caused by the intersection of class, race and gender discriminations aggravates the scenario of black women's health, making them more vulnerable to early pregnancy and to the human immunodeficiency virus (HIV ) (5) .…”
Section: Introductionmentioning
confidence: 99%
“…In health problems associated with the exercise of sexuality, women are particularly affected and because of their biological, have as complication the vertical transmission of diseases such as syphilis, HPV and HIV virus, maternal mortality and morbidity problems, as yet little studied [11].…”
Section: Introductionmentioning
confidence: 99%